Peran Administrasi Sarana dan Prasarana dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar Quran Bakti Ilaahi Bengkulu - Hilman Nugraha; Yola Septia Utami (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: The administration of educational facilities and infrastructure has not played an optimal role, so that the quality of education is still difficult to achieve, marked by planning, procurement, maintenance and recording as well as the elimination of goods have not been fully carried out. The purpose of this research is to map and analyze the role of facilities and infrastructure administration in improving the quality of education in Quran Bakti Ilahi Bengkulu Elementary School. Using descriptive qualitative methods, data collection techniques through interviews, observations, and documentation. Data analysis uses Hubermant's theory. The results of this study show that the quality of education at SD Quran Bakti Ilaahi Bengkulu is generally quite good. This can be seen from the achievement and development of student learning outcomes. From the learning results of SD Quran Bakti Ilaahi students in grade 3 children have been able to memorize 3-10 juz, students are able to read the Quran well in only 3 to 6 months. However, at the level of management of facilities and infrastructure administration, it has not fully played a good role, because there is still improper procurement, maintenance is not optimal, and the recording of facilities and infrastructure does not exist. As a result, the achievement of quality education becomes difficult to realize. So it can be suggested, to improve the quality of education, then increase the role of the administration of educational infrastructure facilities in schools.Keywords: Role, Facilities and Infrastructure Administration, Education Quality, Elementary School. Abstrak: Administrasi sarana dan prasarana pendidikan belum berperan secara optimal, sehingga mutu pendidikan masih sulit dicapai, ditandai dengan perencanaan, pengadaan, pemeliharaan dan pencatatan serta penghapusan barang belum sepenuhnya dilakukan. Tujuan Penelitian ini untuk memetakan dan menganalisis peran administrasi sarana dan prasarana dalam meningkatkan mutu pendidikan di sekolah dasar quran bakti ilaahi bengkulu. Menggunakan metode kualitatif deskriptif, teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Analisis data menggunakan teori Hubermant. Hasil penelitian ini menunjukan mutu pendidikan SD Quran Bakti Ilaahi Bengkulu secara umum sudah cukup baik. Hal ini terlihat dari prestasi dan perkembangan hasil belajar siswanya. Dari hasil belajar siswa SD Quran Bakti Ilaahi di kelas 3 anak-anak sudah mampu menghafal 3-10 juz, siswa mampu membaca al-Quran dengan baik hanya kurun waktu 3 sampai dengan 6 bulan saja. Namun pada tingkat pengelolaan administrasi sarana dan prasarana belum sepenuhnya berperan secara baik, karena masih terdapat pengadaan tidak tepat, pemeliharaan tidap optimal, pencatatan sarana dan prasarana belum ada. Sehingga mengakibatkan pencapaian mutu pendidikan menjadi sulit diwujudkan. Sehingga dapat disarankan, untuk meningkatkan mutu pendidikan, maka tingkatkan peran adminstrasi sarana prasarana pendidikan di sekolah.Kata kunci: Peran, Administrasi Sarana dan Prasarana, Mutu Pendidikan, Sekolah Dasar.